Protective Effects of Methotrexate against Proatherosclerotic Cytokines: A Review of the Evidence - Arduino A. Mangoni; Angelo Zinellu; Salvatore Sotgia; Ciriaco Carru; Matteo Piga; Gian Luca Erre (Mediators of Inflammation)
There is good epidemiological evidence that patients with autoimmune rheumatic disease states, particularly rheumatoid arthritis, have an increased risk of cardiovascular morbidity and mortality when compared to the general population. The presence of a chronic systemic proinflammatory state in this patient group disrupts the structural and functional integrity of the endothelium and the arterial wall, favouring the onset and progression of atherosclerosis. A significant role in the detrimental effects of inflammation on endothelial function and vascular homeostasis is played by specific proatherosclerotic cytokines such as tumour necrosis factor-alpha (TNF-α), interleukin-1 (IL-1), and interleukin-6 (IL-6). Recent systematic reviews and meta-analyses have shown that treatment with methotrexate, a first-line disease-modifying antirheumatic drug (DMARD), is associated with a significant reduction in atherosclerosis-mediated cardiovascular events, such as myocardial infarction and stroke, and mortality, when compared to other DMARDs. This suggests that methotrexate might exert specific protective effects against vascular inflammation and atherosclerosis in the context of autoimmune rheumatic disease. This review discusses the available evidence regarding the potential antiatherosclerotic effects of methotrexate through the inhibition of TNF-α, IL-1, and IL-6 and provides suggestions for future experimental and human studies addressing this issue.